Can Regional Integration Accelerate Development in Africa? : CGE Model Simulations of the Impact of the SADC FTA on the Republic of Madagascar - Hallaert, Jean-Jacques (IMF Working Papers; Working Paper ;, 2007)
Madagascar plans to start phasing out its customs tariffs on imports from the Southern African Development Community in 2007. This paper uses a CGE model to evaluate the impact of the SADC FTA on Madagascar economy. The results suggest that the SADC FTA would only have a limited impact on Madagascar's real GDP because the liberalization affects only a small share of its total imports. However, Madagascar's trade and production pattern would change and benefit the textile and clothing sector. Removing rigidities in the labor and capital market would increase the gains but they would remain limited. Gains from the SADC FTA become substantial only when the regional liberalization is accompanied by a multilateral liberalization.